Care Management Theories versus Realities in Health Care. Issue 5 (20th October 2019) - Wells, Rebecca; Siañez, Mónica; Tamayo, Loida; Breckenridge, Ellen D.; Pennel, Cara
ABSTRACT: Mixed evidence of care management effectiveness raises questions about how these services are provided in practice. This study evaluates care management in nine provider settings using elements from two prominent models: The Chronic Care Model and the Care Transitions Program. Staff interviews addressed organizational and community resources. Patients were also surveyed about their experiences. Patients generally indicated actively managing their own care. However, patient interactions with care managers generally fell below recommended levels. This study suggests a need to examine the quantity of specific elements of care management that yield desired outcomes, such as improved disease self-management and health.